(untitled) (African Journal of Biomedical Research, 2024)
In Nigeria, 151,700 children die every year from diarrhoea disease. The use of a valid and reliable tool for eliciting information on what mothers do at home to manage diarrhoea is critical for healthcare providers and researchers. The study aimed to develop and validate the Home Management of Diarrhoea Assessment Scale (HMDAS) using Rasch Analysis among mothers of under-fives in Nigeria. The cross-sectional survey design was employed among 376 mothers in one selected local government area in each of the 6 geopolitical zones of Nigeria recruited using multi-stage sampling technique. Ethical approval was from Health Research Ethics committee of University of Nigeria Teaching Hospital, Enugu State. Data were collected for 6 months and were subjected to descriptive statistics and Rasch analysis with the aid of SPSS version 23 and jamovi software version 64.2. The HMDAS was developed after indepth literature review and 3 rounds of input from 5 expert reviewers. fit analysis revealed that 12 items were misfits and were expunged from the tool. The HMDAS was found to be unidimensional with eigen value of less than 1. Item and person separation index of the HMDAS were 11.1917 and 2.0123 respectively. Item and the person reliability index of the HMDAS were 0.9121 and 0.0820. The HMDAS was concluded to be a reliable and valid tool for data collection. It was recommended that the HMDAS should be utilized in generating data that can be used for designing interventions aimed at stemming the tide of diarrhoea in Nigeria